Mild cognitive impairment due to Alzheimer disease in the community. Issue 2 (24th September 2013) - Petersen, Ronald C.; Aisen, Paul; Boeve, Bradley F.; Geda, Yonas E.; Ivnik, Robert J.; Knopman, David S.; Mielke, Michelle; Pankratz, Vernon S.; Roberts, Rosebud; Rocca, Walter A.; Weigand, Stephen; Weiner, Michael; et al.
<x xml:space="preserve">Abstract</x> Objective The newly proposed National Institute on Aging–Alzheimer's Association (NIA‐AA) criteria for mild cognitive impairment (MCI) due to Alzheimer disease (AD) suggest a combination of clinical features and biomarker measures, but their performance in the community is not known. Methods The Mayo Clinic Study of Aging (MCSA) is a population‐based longitudinal study of nondemented subjects in Olmsted County, Minnesota. A sample of 154 MCI subjects from the MCSA was compared to a sample of 58 amnestic MCI subjects from the Alzheimer's Disease Neuroimaging Initiative 1 (ADNI‐1) to assess the applicability of the criteria in both settings and to assess their outcomes. Results Fourteen percent of MCSA and 16% of ADNI‐1 of subjects were biomarker negative. In addition, 14% of MCSA and 12% of ADNI‐1 subjects had evidence for amyloid deposition only, whereas 43% of MCSA and 55% of ADNI‐1 subjects had evidence for amyloid deposition plus neurodegeneration (magnetic resonance imaging atrophy, fluorodeoxyglucose positron emission tomography hypometabolism, or both). However, a considerable number of subjects had biomarkers inconsistent with the proposed AD model; for example, 29% of MCSA subjects and 17% of ADNI‐1 subjects had evidence for neurodegeneration without amyloid deposition. These subjects may not be on an AD pathway. Neurodegeneration appears to be a key factor in predicting progression relative to amyloid deposition alone. Interpretation The NIA‐AA criteria apply to most MCI subjects in both the community and clinical trials settings; however, a sizeable proportion of subjects had conflicting biomarkers, which may be very important and need to be explored. Ann Neurol 2013;74:199–208